2009
DOI: 10.35808/ersj/210
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of the Moving Average Strategy and the Episodic Dependencies: Empirical Evidence from European Stock

Abstract: Numerous recent studies are emphasizing the existence of different stock price behaviors, namely long random walk sub periods alternating with short ones characterized by strong linear and/or nonlinear correlations. All these studies suggest that these serial dependencies have an episodic nature. In this paper we investigate the profitability of an optimum moving average strategy selected from 15,000 combinations on the main European capital markets considering the episodic character of linear and/or nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
(14 reference statements)
1
3
1
Order By: Relevance
“…The hypothesis testing results of this study showed that profitability does not affect investors' reactions in Indonesia and Malaysia. This finding contradicts the results of research by Todea, Zoicaş-Ienciu, and Filip (2009), who explained that profitability has a positive influence on the reaction of investors.…”
Section: Effect Of Profitability On Investor Reactioncontrasting
confidence: 99%
“…The hypothesis testing results of this study showed that profitability does not affect investors' reactions in Indonesia and Malaysia. This finding contradicts the results of research by Todea, Zoicaş-Ienciu, and Filip (2009), who explained that profitability has a positive influence on the reaction of investors.…”
Section: Effect Of Profitability On Investor Reactioncontrasting
confidence: 99%
“…Agency theory states that as principals, investors certainly want profits from the funds they invest (Astari et al, 2020). This study is in line with Karamoy et al, (2020) and Todea et al, (2009) that if ROA increases, then the market reaction can directly affect the level of stock prices. The increase of the company attractiveness makes the company more attractive to investors, because the rate of return will be even greater (Zuliarni, 2012).…”
Section: The Effect Of Financial Performance On Investor Reactionssupporting
confidence: 72%
“…Ahmed (2014) employed rolling joint variance ratio test tests, in rolling window procedure and found support for the time-varying market efficiency. Todea et al (2009) verified that implications of AMH and found that the degree of market efficiency varies through time in a cyclical fashion. Urquhart and Hudson (2013) conclude that the AMH describes the behaviour of stock returns better than the EMH.…”
Section: Testing Adaptive Efficiency With Modified Standard Testsmentioning
confidence: 53%
“…Table 1 shows the review matrix for return predictability studies and Table 2 shows the review matrix for price-volume relationship studies. (Khuntia and Pattanayak 2018;Kim et al 2011) Linear long memory R/S, Spectral Regression (Barkoulas et al 2000) MF-DFA, R/S (Hull and McGroarty 2014) Nonlinear long memory modified R/S, ESTAR unit root test (Gozbasi et al 2014) MF-DFA, Modified R/S analysis (Todea et al 2009) Linear unit root ADF, PP, DF-GLS, NP, KPSS or VR test (Konak andŞeker 2014), (Gupta and Yang 2011) -Note: VR = variance ratio, AVR = automatic variance ratio, AQ = automatic portmantau, GS = generalized spectral. R/S = rescaled range, MF-DFA = multifractal detrended fluctuation analysis.…”
Section: Introductionmentioning
confidence: 99%